1977
DOI: 10.1042/cs0520457
|View full text |Cite
|
Sign up to set email alerts
|

Catabolic rate of α1-antitrypsin of Pi type M and Z in man

Abstract: 1. Human alpha1-antitrypsin was isolated from three Pi M and two Pi Z subjects without alteration of its microheterogeneity. The purified proteins were labelled with either 125I or 131I by a lactoperoxidase method. 2. The disappearance rate of two types of alpha1-antitrypsin were studied after simultaneous injection of labelled M-protein and Z-protein into Pi M subjects. 3. The ratio of extravascular to plasma pools of alpha1-antitrypsin ranged between 1-2 and 1-6 with no difference between M- and Z-protein. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
1
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
4
14
1
1
Order By: Relevance
“…The plasma volume of our patient was normal, thus excluding the possibility that a smaller volume of distribution is the reason for the high 0q-antitrypsin concentration. The halflifes of 7,5 and 8 days found for the normal volunteers compare well with those of 6.0-7.2 days found by Laurell and coworkers for 0q-antitrypsin of the same phenotype [10]. In our patient, the half-life was prolonged to 15 days.…”
Section: Discussionsupporting
confidence: 86%
“…The plasma volume of our patient was normal, thus excluding the possibility that a smaller volume of distribution is the reason for the high 0q-antitrypsin concentration. The halflifes of 7,5 and 8 days found for the normal volunteers compare well with those of 6.0-7.2 days found by Laurell and coworkers for 0q-antitrypsin of the same phenotype [10]. In our patient, the half-life was prolonged to 15 days.…”
Section: Discussionsupporting
confidence: 86%
“…Although human PiM livers normally synthesize sufficient AAT to maintain plasma levels at 1.35 g/liter (31) with a t1/2 of 32 (34). The number of AAT-positive cells was correlated with gene copy number and plasma AAT levels.…”
Section: Discussionmentioning
confidence: 99%
“…49 In addition, in contrast to current bypassing agents, which are administered intravenously, the subcutaneous route of administration for KRK a 1 AT might also be available. Studies in rabbits showed that the pharmacodynamics of subcutaneously administered plasma human a 1 AT were comparable to intravenously administrated protein.…”
mentioning
confidence: 99%